Dampak Perilaku Patologis terhadap Kesehatan Remaja: Tinjauan Literatur Sistematis - Ali Amran; Esli Zuraidah Siregar; Nurharisyah Hasibuan; Salsabila Nasution (Jurnal Penelitian Pendidikan IPA, 2025)
Adolescence is a critical transitional stage marked by vulnerability to negative influences, including drug abuse, classified as pathological behavior. Such abuse not only harms physical health but also poses serious risks to mental and social well-being. This study systematically examines the impact of drug abuse on adolescent health using findings from empirical research. A systematic literature review was conducted following PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Articles were retrieved from the Scopus database with inclusion criteria: publications from 2016–2025, in English, and focusing on adolescents aged 12–19 years. Descriptive analysis was applied to identify health impact patterns. From 10 eligible studies, results showed that adolescent drug abuse is strongly associated with psychological disorders, including depression, anxiety, sleep disturbances, and suicidal behavior. Physical consequences include impaired nervous system function and weakened immunity. These findings indicate that drug abuse exerts multidimensional harm, disrupting overall adolescent development. The review also identifies potential interventions, such as medication-assisted treatment, family-based approaches, and gamification to enhance engagement. These strategies highlight the need for integrated prevention and rehabilitation programs. The evidence can guide policymakers, educators, and healthcare providers in designing measures to reduce adolescent drug abuse and its long-term consequences.